Quaternary geology and biology of the Jørgen Brønlund Fjord area, North Greenland - Bennike, Ole (Meddelelser om Grønland. Geoscience, 1987)
Prior to the last deglaciation, probably in the Late Weichselian, glaciers draining the Inland Ice were present in Independence Fjord and Jørgen Brønlund Fjord. and a glacier draining an ice cap in the north was present in the Børglum Elv valley. It is proposed that glacier fronts were situated at the mouth of Jørgen Brønlund Fjord during a halt in the deglaciation 8000-9000 years BP, and that this halt led to a low initial rate of emergence. Jørgen Brønlund Fjord was deglaciated 8000-7600 years BP. The early Holocene marine limit is c. 65 m above sea-level in the fjord, and c. 80 m east of the fjord. The slow initial rate of emergence was soon followed by rapid emergence. Emergence of the land continued until about 1000 years BP. Part of the marine invertebrate fauna was established just after deglaciation. The same probably applies to the terrestrial flora and fauna. By 6000 years BP entry of driftwood and southern marine mammals began, and it continues today. Around 4000 years BP the Independence I people made their appearance, later the Independence II people and the Thule eskimos inhabited the area. The geomorphological features show a resemblance to those from valleys in Antarctica.